Comparative legal analysis of certain provisions of the legislation of the Republic of Kazakhstan and Ukraine on the adoption of a child - Aliyeva, L.R.; Klyuyeva, Ye.N. (Bulletin of the Karaganda University “Law Series”, 2023)
In the framework of this research, some features of the institution of adoption of a child in the Republic of Kazakhstan and Ukraine are considered. The authors analyze the legal concept of “adoption”, the composition of the persons involved in the adoption of a child in civil proceedings. Questions about persons who are subject to adoption and persons who may act as adoptive parents according to the legislation of each of the states are considered. Attention was paid to various scientific views available in the doctrinal sources regarding the definition of “adoption”. The authors draw attention to the fact that, according to some similar provisions of the institution under consideration, there are still certain differences in the norms of Kazakhstan and Ukrainian legislation. The analysis of legal norms regulating the procedure for considering cases of adoption of a child in the courts of the Republic of Kazakhstan and Ukraine was conducted. The methodological basis of this scientific work was a dialectical, systemic, comparative legal, normative and other methods of cognition. The norms of basic international legal acts governing this area of relations are taken into account. The article also discusses the possibility of reducing the age of 10, the child to be adopted in the Republic of Kazakhstan in order to receive his consent to adoption.